Content validation of an instrument for medical record audits - Carla Simplicio; Ariane Polidoro Dini (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: To build and validate the content of an instrument to conduct medical record audits; to conduct a pre-test. Methods: Methodological study conducted from May/2020 to May/2021 in three stages: 1) development of the instrument by bibliographic survey and benchmarking; 2) content validation using the Delphi technique; 3) application of the instrument and descriptive analysis in a sample of 200 medical records. Results: An instrument was constructed with 11 domains containing sub-items that characterize the quality of care. Two stages of the Delphi technique were necessary to reach a content validity index higher than 0.90. For each domain, a graduated scale with a numerical value from 1 to 4 points was attributed, reflecting the quality of its completion. The average time of application was 35 minutes per record. Conclusions: The tool proved to be viable to support clinical audits to identify the level of excellence and reveal opportunities for improvement in care processes.